Digitalizing the Living Qur'an: Religious Authority and the Transformation of Qur'anic Knowledge in Indonesia - Ahmad Syukron; Randy Putra Alamsyah; Romlah Widayati; Dedi Masri; Muhammad Muammar Alwi (JURNAL INDO-ISLAMIKA, 2026)
This article examines the digitalization of the Living Qur’an in Indonesia by analyzing how Qur’anic knowledge is produced, circulated, authorized, and received through digital platforms. The study responds to a central scholarly problem: digital media have expanded public access to Qur’anic learning, yet they have also transformed the basis of religious authority, interpretive legitimacy, and everyday Qur’anic reception. Using a qualitative research design that combines digital ethnography and qualitative content analysis, this study analyzes publicly available Qur’anic discourse on YouTube, Instagram, TikTok, and Indonesian tafsir websites, including long-form tafsir lectures, short-form Qur’anic content, digital tafsir materials, and audience interactions. The findings show that digital platforms have become new infrastructures of Qur’anic knowledge, making the Qur’an searchable, portable, shareable, and continuously embedded in everyday digital life. The study also finds that tafsir authority is no longer shaped solely by sanad, scholarly credentials, pesantren affiliation, or institutional recognition, but is increasingly negotiated through media visibility, communicative style, audience trust, and algorithmic circulation. Furthermore, digital Qur’anic knowledge increasingly shifts from textual-systematic tafsir toward practical moral pedagogy addressing worship, family life, anxiety, repentance, social ethics, and personal spirituality. Digital audiences also participate in constructing Qur’anic reception through comments, questions, sharing, and public engagement. The article contributes theoretically by extending Living Qur’an studies into digital religion scholarship and proposing digital Qur’anic reception as a mediated socio-religious formation shaped by scripture, authority, technology, and participatory audiences.